Konsep Jenis Lembaga Jaminan Utang Pada koperasi - Gunawan Gunawan (Universitas Islam Nusantara, 2022)
In the practice of binding debt guarantees in the Rukun Mekar Savings and Loans Cooperative, there is a conflict between das sollen and das sein, or there is an imbalance between reality/empirical and ideal conditions, namely, regarding the provision of loans with collateral without being encumbered by mortgage or fiduciary rights. The reason for this is that the process of imposing mortgage rights, or fiduciary, is not a simple process, takes a long time and costs a lot of money. Based on these problems, this study aims to find out about the concept of types of debt guarantee institutions in cooperatives, which are different from mortgages, fiduciaries, pledges, mortgages, and warehouse receipts. The research specification is descriptive analytical, with a normative juridical approach, using the main source of secondary data, and the research is carried out in one stage, namely, library research, which is supported by interviews using data collection techniques consisting of library research and interviews, then secondary data and interviews. The results of the interviews inventoried were analyzed qualitatively normatively. This study found the results: the concept of a type of debt guarantee institution in cooperatives, is a concept that offers debt guarantee institutions that apply specifically to cooperatives that are different from mortgage, fiduciary, mortgage, mortgage, and warehouse receipt institutions, the agreement is made in the form of a deed. under a binding hand, the object of the guarantee is all objects, whether movable or immovable, tangible or intangible, whether existing or will be owned by the borrower, which gives a preferred position to the cooperative, the process is simple, fast, low cost, and also has the executive power of slag, namely the object of debt guarantees can be executed by force by the cooperative, if the borrower defaults, without the need for a civil court process, so as to provide legal certainty, justice, and benefit to the parties, especially the cooperatives.